2020
DOI: 10.26434/chemrxiv.12977597.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical Insights into the Effect of Halogenated Substituent on the Electronic Structure and Spectroscopic Properties of the Favipiravir Tautomeric Forms and Its Implications on the Treatment of COVID-19

Abstract: <p>In this study, we systematically investigated the electronic structure, spectroscopic (nuclear magnetic resonance, infrared, Raman, electron ionization mass spectrometry, UV-Vis, circular dichroism, and emission) properties, and tautomerism of halogenated favipiravir compounds (fluorine, chlorine, and bromine) from a computational perspective. Additionally, the effects of hydration on the proton transfer mechanism of the tautomeric forms of the halogenated favipiravir compounds are discussed. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…In our previous work, we estimated the EI-MS spectra and identi ed the possible trajectories for the Favipiravir molecule and its tautomers. 12 In the current work, we expanded our analysis to evaluate each intermediary species' biochemical activity. The computed EI-MS spectrum of Favipiravir has two main trajectories that yield similar species (Figure 1 (a)).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we estimated the EI-MS spectra and identi ed the possible trajectories for the Favipiravir molecule and its tautomers. 12 In the current work, we expanded our analysis to evaluate each intermediary species' biochemical activity. The computed EI-MS spectrum of Favipiravir has two main trajectories that yield similar species (Figure 1 (a)).…”
Section: Resultsmentioning
confidence: 99%
“…37 As a result, it is important to note that the values extracted from RMSD (5R82 = 0.94 Ǻ / 3H5Y = 1.55 Ǻ) showed that the program used in this study is adequate for predicting the conformation that the co-crystallized ligands adopted experimentally within the viral M pro and RdRp of SARS-CoV-2. 12,13,38 The re-docking con gurations were maintained to perform the docking calculations of the drugs investigated as well as their metabolism fragments. All computed interaction energy results are exhibited in Table 1.…”
Section: Docking Results and Admetmentioning
confidence: 99%
See 3 more Smart Citations